Paradoxical miliary tuberculomas in the brain in an immunocompetent case of pulmonary miliary tuberculosis: A case report (Indian Journal of Case Reports, 2026)
Paradoxical reactions are immune-mediated de novo or worsening manifestations after initial improvement in a tubercular case during antitubercular therapy (ATT). Here, we report a young immunocompetent female diagnosed with miliary tuberculosis (TB), complicated by new and acute onset headache, vomiting, and left-sided weakness on the 15th day of ATT. Neuroimaging revealed multiple new ring-enhancing lesions consistent with miliary intracranial tuberculomas in the cortex, basal ganglia, and cerebellum. Treatment failure, drug resistance, alternative infections, malignancy, and drug toxicity were excluded. A paradoxical reaction as military tuberculoma in the brain was diagnosed. Initiation of corticosteroids resulted in rapid neurological improvement and radiological resolution by 8 weeks. Recognizing paradoxical intracranial tuberculomas early is essential to avoid misclassification as drug-resistant TB. Continued ATT with timely corticosteroid therapy leads to favorable outcomes.